1998
DOI: 10.1038/sj.onc.1201614
|View full text |Cite
|
Sign up to set email alerts
|

hSmad5 gene, a human hSmad family member: its full length cDNA, genomic structure, promoter region and mutation analysis in human tumors

Abstract: hSmad (mothers against decapentaplegic)-related proteins are important messengers within the Transforming Growth Factor-b 1 (TGF-b 1 ) superfamily signal transduction pathways. To further characterize a member of this family, we obtained a full length cDNA of the human hSmad5 (hSmad5) gene by rapid ampli®cation of cDNA ends (RACE) and then determined the genomic structure of the gene. There are eight exons and two alternative transcripts; the shorter transcript lacks exon 2. We identi®ed the hSmad5 promoter re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

1999
1999
2005
2005

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 19 publications
1
20
0
Order By: Relevance
“…Some data argue against this notion: (a) at the genomic level point mutations possibly inactivating one allele appear to be extremely rare Gemma et al, 1997;Thiagalingam et al, 1996); (b) aberrant mRNA transcripts are mostly accompanied by an often predominant wt mRNA fragment, and abnormal FHIT mRNA transcripts are also found in various normal tissues (Gayther et al, 1997;Panagopoulos et al, 1997;van den Berg et al, 1997;Wang et al, 1998); (c) aberrant transcripts are not consistently translated into truncated protein; and (d) replacement of FHIT protein in human carcinoma cells does not always suppress tumour cell growth implying that FHIT is perhaps involved in tumorigenesis along pathways distinct from the classical tumour suppressor mechanism (Otterson et al, 1998). On the other hand some data suggest that the wt FHIT gene product might exert tumour-suppressing activity: (a) in contrast to normal cells which invariably express normal FHIT protein, the protein may be absent in solid tumours Greenspan et al, 1997;Sozzi et al, 1997).…”
Section: Discussionmentioning
confidence: 94%
“…Some data argue against this notion: (a) at the genomic level point mutations possibly inactivating one allele appear to be extremely rare Gemma et al, 1997;Thiagalingam et al, 1996); (b) aberrant mRNA transcripts are mostly accompanied by an often predominant wt mRNA fragment, and abnormal FHIT mRNA transcripts are also found in various normal tissues (Gayther et al, 1997;Panagopoulos et al, 1997;van den Berg et al, 1997;Wang et al, 1998); (c) aberrant transcripts are not consistently translated into truncated protein; and (d) replacement of FHIT protein in human carcinoma cells does not always suppress tumour cell growth implying that FHIT is perhaps involved in tumorigenesis along pathways distinct from the classical tumour suppressor mechanism (Otterson et al, 1998). On the other hand some data suggest that the wt FHIT gene product might exert tumour-suppressing activity: (a) in contrast to normal cells which invariably express normal FHIT protein, the protein may be absent in solid tumours Greenspan et al, 1997;Sozzi et al, 1997).…”
Section: Discussionmentioning
confidence: 94%
“…RNA isolation, cDNA array hybridisation and analysis of hybridisation signals Total RNA was isolated from each cell line using standard protocols described previously (Gemma et al, 1996(Gemma et al, , 1998. Messenger RNA was then purified from total RNA by incubation with oligo-dT-magnetic beads (Toyobo Co., Osaka, Japan).…”
Section: Drugs and Growth-inhibition Assaymentioning
confidence: 99%
“…Polymerase chain reaction -single strand conformation polymorphism (PCR -SSCP) analysis was performed as previously described (Gemma A, et al, 1996(Gemma A, et al, , 1998. Each of the three exons (18, 19 and 21) of the EGFR gene was amplified separately using reported PCR primers (Lynch et al, 2004).…”
Section: Mutation Analysis Of the Egfr Genementioning
confidence: 99%
See 1 more Smart Citation
“…The reason for this apparent anomaly is unclear, however, a recent report has described the existence of an antisense transcript of Smad5, DAMS, which has been suggested to regulate translation of Smad5. 30 Our analysis of 5 different targets has shown that in all cases antibodies specific to gene-derived peptide sequences can be isolated when a maximum of 2 peptides are synthesized per gene. In n ϭ 2/5 (40%) of the gene targets we were able to isolate antibodies that showed specificity for a protein product of the expected molecular weight in Western blotting and gave a specific staining pattern in immunohistochemistry.…”
Section: Use Of Peptide Specific Phage Antibodies As Probes For the Pmentioning
confidence: 99%